Attitudes to incorporating genomic risk assessments into population screening programs: the importance of purpose, context and deliberation. Issue 1 (December 2016) - Nicholls, Stuart; Etchegary, Holly; Carroll, June; Castle, David; Lemyre, Louise; Potter, Beth; Craigie, Samantha; Wilson, Brenda
Abstract Background The use of an overall risk assessment based on genomic information is consistent with precision medicine. Despite the enthusiasm, there is a need for public engagement on the appropriate use of such emerging technologies in order to frame meaningful evaluations of utility, including the practical implementation and acceptability issues that might emerge. Doing so requires the involvement of the end users of these services, including patients, and sections of the public who are the target group for population based screening. In the present study we sought to explore public attitudes to the potential integration of personal genomic profiling within existing population screening programs; and to explore the evolution of these attitudes as part of a deliberative process. Methods We conducted a mixed methods study presented in the format of a deliberative workshop. Participants were drawn from communities in Ottawa, Ontario (ON) and St John's, Newfoundland and Labrador (NL), Canada. Individuals were approached to take part in a workshop on the incorporation of genomic risk profiling for either colorectal cancer screening (CRC), or newborn screening for type 1 diabetes mellitus (T1DM). Results A total ofN = 148 (N = 65 ON, N = 83 NL) participants provided data for analysis. Participants in both groups were supportive of public funding for genomic risk profiling, although participants in the T1DM groups expressed more guarded positive attitudes than participants in the CRC groups. These views were stable throughout the workshop (CRC, p = 0.15, T1DM, p =0.39). Participants were less positive about individual testing, with a significant decrease in support over the course of the workshop (CRCp = 0.02, T1DM, p = 0.003). Common concerns related to access to test results by third parties. Conclusions The findings of this study suggest that members of the target populations for potential genomic profiling tests (designed for screening or risk prediction purposes) can engage in meaningful deliberation about their general acceptability and personal utility. Evaluations of whether a test would be personally useful may depend on the experience of the participants in personal health decision making, the purpose of the test, and the availability of interventions to reduce disease risk.